Factors Affecting Academic Self-Efficacy and Its impact on perceived Academic Burnout among Students in Bangladesh. - Sraboni Akter (Research Synergy Foundation, 2021)
For this present study, COR and SCT theory was used firstly to examine the factors related to academic burnout meanwhile, secondly, this research also attempts to examine the factors related to academic self-efficacy and Finally, to identify the relationship between academic self-efficacy academic burnout in Khulna city, Bangladesh. For this present study data was collected via both E-mail and self-administrative questionnaire from 272 university students. From the research findings and analysis, it was found out that all the p-values for all the variables were found to be less than 0.05, an indication that was statistically significant for all variables especially. The relationship between Academic self-efficacy and Academic Burnout is (?=.506, Sig. =0 .00) which was statistically significant and all the results are supported by the previous studies.